2017
DOI: 10.1130/ges01479.1
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional assessment of reformed teaching practice in geoscience classrooms

Abstract: This study analyzed quantitative and qualitative data from classroom observations combined with instructor survey results to characterize the application of reformed teaching practices in undergraduate geoscience classes in the United States. Trained observers used the Reformed Teaching Observation Protocol (RTOP) to score 204 geoscience classes. Observed faculty represent a diversity of institutions, teaching rank, and years of experience. Classrooms observed included introductory and upper-level undergraduat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 48 publications
4
54
0
Order By: Relevance
“…1c), it was common for them to report lecture as a primary mechanism when we asked about methods of engaging their students (as opposed to asking what the instructor would be doing). This also fits with a number of recent studies that have characterized the heavy utilization of lecture-based instruction within higher education STEM classrooms (Apkarian & Kirin, 2017;Stains et al, 2018;Teasdale et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1c), it was common for them to report lecture as a primary mechanism when we asked about methods of engaging their students (as opposed to asking what the instructor would be doing). This also fits with a number of recent studies that have characterized the heavy utilization of lecture-based instruction within higher education STEM classrooms (Apkarian & Kirin, 2017;Stains et al, 2018;Teasdale et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies have begun to illuminate population-level patterns in learning experiences within the postsecondary STEM classroom. In geoscience, survey results were combined with classroom observation data to characterize over 200 courses (Teasdale et al, 2017). Within this broad sample, 25% of classes were classified as student centered, 45% of classes were classified as transitional, and 30% of classes were classified as teacher centered.…”
Section: Engaging Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Although both of the data sets examined in this study are self-reported, Teasdale et al (2017) found a strong correlation between self-reports of the frequency of use of in-class exercises and observations of student-student interactions, group work, and discussion. The classrooms where these behaviors were observed were classified as "student-centered," which constituted 25% of the total they observeda similar proportion to the proportion of instructors who reported using in-class exercises and/or small-group discussion in every class in 2016 (Fig.…”
Section: Teamwork Collaboration and Discoursementioning
confidence: 65%
“…In higher education, instructors are faced with overlapping professional obligations and teaching support and constraints from their institution, department, and peers [14,15]. While past research has explored some of these influences on teaching practices, few studies have taken a multidimensional approach to exploring the factors that influence teaching of learner-centered courses [16][17][18]. As part of a longitudinal study of the Faculty Institutes for Reforming Science Teaching (FIRST) IV program [19,20], we sought to tease apart the relative factors that drive the implementation of learnercentered teaching practices.…”
Section: Introductionmentioning
confidence: 99%